Microplastics in commercially sold fishes in Tacloban City, Leyte, Philippines - Benaires, Kenney D.
A KAP survey was done to provide insights into the knowledge, attitudes, and perceptions of local communities in Tacloban City regarding microplastics. The respondents, who were mostly young and educated adults, gained knowledge about microplastics from personal experiences. They had a positive attitude towards reducing plastic pollution and recognized the importance of coastal waters. With a significant number of people who are still willing to consume fish with microplastics, it is recommended to raise awareness about the potential health risks associated with consuming fish containing microplastics and promote sustainable practices to reduce plastic pollution in order to mitigate the ingestion of microplastics through seafood consumption. Future research should explore sustainable alternatives to single-use plastics, conduct broader social surveys, compare microplastics in sediments and water, and investigate the accumulation of microplastics in fish muscle tissues.